Secrets of podcasting : audio blogging for the masses - Farkas, Bart (Peachpit Press, 2006)
Whether you want to create your own podcasts or just would like to locate and then listen to audio programs on your portable player, this is the book for you. In Secrets of Podcasting, Second Ed ition, author Bart G. Farkas provides real-world guidance and advice on how to: Download and enjoy podcasts with any MP3 player Create a script and set the structure and flow of your audio or video podcast Choose the right equipment-including the right microphone, headphones, and even preamp Use a digital recording device instead of your PC or Mac Pick audio editing and recording software Legally play music in your podcast or vodcast Distribute your podcast or vodcast In addition, Bart includes tutorials on creating podcasts on Windows machines and on Macs. He also offers dozens of recommendations for software to use for finding and subscribing to podcasts.